Encapsulation of enzyme by metal-organic framework for single-enzymatic biofuel cell-based self-powered biosensor. (February 2020) - Li, Xin; Li, Dawei; Zhang, Yanan; Lv, Pengfei; Feng, Quan; Wei, Qufu
Abstract: Self-powered biosensor, as a new sensing platform, utilizes biofuel cells as synchronous power source and biosensor system, with the advantages of no external power source, simple instrumentation and easy miniaturization. Meanwhile, inspired by biomimics for the encapsulation of soft tissue within protective exteriors in nature, encapsulation of biological macromolecules by metal organic-frameworks (MOFs) have been proved to be an effective strategy for enhancing the biocatalytic activity in maintaining biological functions. Herein, we successfully encapsulated laccase (LAC) in zeolitic imidazolate framework-8 (ZIF-8) and combined it with bacterial cellulose (BC)/carboxylated multi-walled carbon nanotubes (c-MWCNTs) skeleton to prepare highly flexible BC/c-MWCNTs/ZIF-8@LAC electrode. Subsequently, we ingeniously designed an highly flexible self-powered sensing platform based on biofuel-cell driven by single-enzyme, harvesting bisphenol A (BPA) as a model analyte. The maximum power density (Pmax ) of single-enzymatic biofuel cell (EBFC) exhibited an excellent linear dynamic range from 0.01 to 0.4 mM with a lower detection limit of 1.95 × 10 −3  mM for BPA concentrations. Therefore, the designed single-EBFC-based self-powered sensor is feasible in BPA detection and has a broad application prospect in the field of water pollutants detection. Graphical abstract: Image 1 Highlights: A biocatalyst of ZIF-8@LAC with unprecedented stability was prepared. A single-enzymatic biofuel cell-based self-powered biosensor was established. The designed device exhibits excellent detection sensitivity to BPA.